Assessment of mobile invertebrates associated with mats of the red alga Phyllophora crispa at Giglio Island, Mediterranean Sea - Töpfel, Alexander; Steinhoff, Melissa; Wild, Christian (PANGAEA, 2025)
Dataset on the epibenthic abundance of mobile invertebrates on P. crispa habitats at two study sites (Fenaio and Secca II) in the NW Mediterranean Sea (Giglio Island, Italy). Samples were obtained via SCUBA diving using a newly designed sampling device appropriate for mobile fauna in June 2023 and analyzed by microscopic determination and counting of specimens. The dataset includes details on the sampling efforts, diversity indices (Shannon (H'), Pielou (J'), Simpson (D)), and densities of organisms per m² seafloor. The number of individuals per family was counted. Densities of mobile invertebrates were extrapolated using wet weights and measured surface area of P. crispa samples. Detailed descriptions of the calculations can be found in the corresponding publication (Töpfel et al. 2025).
Keywords: ecosystem engineers; Epifauna; invertebrates; Mediterranean Sea; Phyllophora crispa